Ultrasound-Promoted Regioselective Synthesis of 1-Aryl-5-amino-1H-tetrazoles - Habibi, Davood; Nasrollahzadeh, Mahmoud; Sahebekhtiari, Hesam; Sajadi, S. Mohammad (Synlett, 2012)
A new method for the regioselective synthesis of 1-aryl-5-amino-1H-tetrazoles has been developed by the reaction of arylcyanamides with sodium azide using ZnCl2 under ultrasound irradiation in excellent yields.
Keywords: 1-aryl-5-amino-1H-tetrazole; cyanamide; sodium azide; ZnCl2; sonochemical switching